Quantitative Proteomic Analysis in Alveolar Type II Cells Reveals the Different Capacities of RAS and TGF-β to Induce Epithelial–Mesenchymal Transition - Zhou, Yilu; Hill, Charlotte; Yao, Liudi; Li, Juanjuan; Hancock, David; Downward, Julian; Jones, Mark G.; Davies, Donna E.; Ewing, Rob M.; Skipp, Paul; Wang, Yihua (Frontiers in Molecular Biosciences, 2021)
Alveolar type II (ATII) epithelial cells function as stem cells, contributing to alveolar renewal, repair and cancer. Therefore, they are a highly relevant model for studying a number of lung diseases, including acute injury, fibrosis and cancer, in which signals transduced by RAS and transforming growth factor (TGF)- play critical roles. To identify downstream molecular events following RAS and/or TGF- activation, we performed proteomic analysis using a quantitative label-free approach (LC-HDMSE) to provide in-depth proteome coverage and estimates of protein concentration in absolute amounts. We chose ATIIER:KRASV12 as an experimental cell line in which RAS is activated by adding 4-hydroxytamoxifen (4-OHT). Proteomic analysis of ATII cells treated with 4-OHT or TGF-β demonstrated that RAS activation induces an epithelial–mesenchymal transition (EMT) signature. In contrast, under the same conditions, activation of TGF-β signaling alone only induces a partial EMT. EMT is a dynamic and reversible biological process by which epithelial cells lose their cell polarity and down-regulate cadherin-mediated cell–cell adhesion to gain migratory properties, is involved in embryonic development, wound healing, fibrosis and cancer metastasis. Thus, these results could help to focus research on the identification of processes that are potentially driving EMT-related human disease.